Investigations of Y-89(p,x)Zr-86,Zr-88,Zr-89g, Y-86m+g,Y-87g,Y-87m,Y-88g, Sr-85g, and Rb-84g nuclear processes up to 42 MeV - Khandaker, Mayeen Uddin; Otuka, N.; Kim, G.; Kim, K.; Lee, M.W.; Kim, K.S. (Elsevier, 2012)
Production cross-sections of the Y-89(p,x)Zr-86,Zr-88,Zr-89g, Y-86m+g,Y-87g,Y-87m,Y-88g, Sr-85g, and Rb-84g nuclear processes were investigated up to 42-MeV proton energy by using a stacked-foil activation technique at the MC-50 cyclotron of the Korea Institute of Radiological and Medical Sciences. Cumulative cross-sections of the Y-88g radionuclide have been reported here for the first time from proton activation on natural yttrium target. The present data were compared with the available experimental data as well as theoretical calculations based on the TALYS and the ALICE-IPPE codes, and found in general good agreement among them. Due to the mono-isotopic characteristics of the natural yttrium, the investigated Y-89(p,x)Zr-86,Zr-88,Zr-89g, Y-86m+g,Y-87g,Y-87m,Y-88g, Sr-85g, and Rb-84g processes are suitable for testing of nuclear reaction theories and/or mechanism. A quantitative analysis has also done to understand more accurately the predictive power of the model codes by performing calculations of deviation factors between the measured data and respective model calculations. The thick target integral yields, i.e., induced radioactivity per unit fluence of 42-MeV protons were also deduced from the measured cross-sections of the investigated radionuclides. Optimal production pathway for the Zr-89-PET radionuclide using a cyclotron is discussed elaborately. The measured cross-sections of Y-87g, Y-88g, Zr-88, and Zr-89g radionuclides find importance due to their suitable decay characteristics leading to medical and thin layer activation applications. In addition, the present experimental results will play an important role in enrichment of the literature data base for proton-induced reactions on natural yttrium leading to various applications. (C) 2011 Elsevier B.V. All rights reserved.